2021
DOI: 10.1111/anu.13256
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of Bacillus subtilis and Enterococcus faecalis can effectively improve the growth performance, immunity, and resistance of tilapia against Streptococcus agalactiae

Abstract: The combined probiotics (four different combination of Bacillus subtilis, Bacillus licheniformis and Enterococcus faecalis) were used and the growth performance, immunity, gut morphology and resistance to Streptococcus agalactiae of tilapia (Oreochromis mossambicus) were comprehensively evaluated after 42 days feeding on supplemented diets. Results showed that the growth performance of tilapia in PG2 (with B. subtilis and E. faecalis) was the best. Moreover, the strong positive association of some indices with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Herein, BS and CS can significantly improve the growth performance of GIFT tilapia, reduce CF, and contribute significantly to growth enhancement. According to the findings of Liu et al ., bacillus subtilis can provide a better intestinal flora environment for tilapia as well as improve intestinal absorption and metabolism of nutrients to promote tilapia growth [ 25 ]. Similarly, CS can promote tilapia growth by increasing feed conversion rate [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Herein, BS and CS can significantly improve the growth performance of GIFT tilapia, reduce CF, and contribute significantly to growth enhancement. According to the findings of Liu et al ., bacillus subtilis can provide a better intestinal flora environment for tilapia as well as improve intestinal absorption and metabolism of nutrients to promote tilapia growth [ 25 ]. Similarly, CS can promote tilapia growth by increasing feed conversion rate [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have shown that NO and its oxygen metabolites are released into serum when macrophages and some non-immune cells are activated [ 45 ], which play a role in signal transduction and scavenging oxygen free radicals in the body [ 46 ]. Many studies have shown that adding BS to feed can increase the activities of LZM, SOD, ACP and AKP, and T-AOC in the serum of GIFT tilapia [ 25 ]. Similarly, CS can promote tilapia growth and improve SOD, LZM, and other enzyme activities in serum, thus enhancing the disease resistance to Aeromonas hydrophila [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they aid in the development of the host's digestive system, maintain the balance of intestinal microbiota, and influence the structure of the intestines (Allameh et al, 2016;Dagá et al, 2013). Therefore, probiotics have become vital ingredients in feed supplements, while improving the immune system and growth functions as abovementioned, also inhibiting the growth of pathogens (Amir et al, 2019Tachibana et al, 2021;Moustafa et al, 2021;El-Saadony et al, 2021;Liu et al, 2021;Hassaan et al, 2021). They are a successful and environmentally friendly alternative to antibiotics, improving rearing water quality and the fish's response to stress (Elsabagh et al, 2018).…”
mentioning
confidence: 99%